Konstruksi Hukum Investasi Kripto dalam Sistem Hukum Ekonomi Syariah Perspektif Maqashid Syariah - Muhammad Nur Karim Al Ismariy; Luthfi Eka Wispriyanti; Lailasari Ekaningsih; Ridho Saadillah Ahmad; Irfan Rizky Hutomo (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2026)
The rapid development of digital technology has introduced cryptocurrency as a new investment instrument that raises complex legal issues, particularly within the framework of Islamic economic law. In Indonesia, cryptocurrencies are legally recognized as tradable commodities but are not permitted as lawful means of payment. Meanwhile, Islamic law provides conditional permissibility for crypto investment, as reflected in the Fatwa of the National Sharia Council of the Indonesian Ulama Council (DSN-MUI) No. 140/DSN-MUI/XI/2021. This study aims to analyze the legal construction of cryptocurrency investment within the Indonesian Islamic economic law system, examine its legality under both positive law and Islamic law, and assess its conformity with maqashid al-sharia principles. This research employs a qualitative method with a normative juridical approach, relying on library research of statutory regulations, sharia fatwas, and relevant academic literature. The findings indicate that cryptocurrency investment may be legally acceptable under certain conditions, provided that it is conducted transparently, based on clear contractual arrangements, and free from elements of gharar, maysir, and excessive speculation. The maqashid al-sharia approach plays a crucial role in evaluating the protection of wealth and ensuring public benefit in digital investment practices.